Dinamika Living Law: Peran Hukum Adat Bersih Desa dalam Menjaga Kohesi Sosial Masyarakat Lokal Ponorogo: Hukum Adat - Maria Yosepin Endah Listyowati; Prasetyo Hadi Prabowo; Selvia Wisuda; Reza Fitriansyah; Frans Geraldo Hetaria (Yayasan Literasi Sains Indonesia, 2025)
Indonesia with all its cultural diversity and society, continues to experience social transformation triggered by changes in cultural values. Nevertheless, customary law still plays a vital role in community life, especially in the socio-social dimension. As part of the cultural area of East Java, Ponorogo customary law is inherently influenced by three main pillars: Javanese harmonious values, Islamic teachings, and local beliefs. One of the cultural heritages that preserves this customary law is the tradition of Bersih Desa, which is still carried out for generations. More than just a cultural ritual, Bersih Desa actually has a living law dimension in society. This tradition features the existence of unwritten rules that are binding, manifested in social obligations for citizens, such as participation in community service, joint contributions, and salvation prayers. The norm of mutual cooperation that is manifested in this joint work reflects social solidarity and the value of togetherness which is the core of Javanese customary law. In addition, there are customary sanctions imposed on those who neglect these obligations. The main function of the implementation of Bersih Desa is to strengthen community harmony, maintain social cohesion, and strengthen harmony between humans, nature, and ancestors. Thus, this tradition is a customary law practice with high cultural value.